2021
DOI: 10.3390/ijms222413579
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs: Recent Insights into Their Role in Male Infertility and Their Potential as Biomarkers and Therapeutic Targets

Abstract: Long noncoding RNAs (lncRNAs) are composed of nucleotides located in the nucleus and cytoplasm; these are transcribed by RNA polymerase II and are greater than 200 nt in length. LncRNAs fulfill important functions in a variety of biological processes, including genome imprinting, cell differentiation, apoptosis, stem cell pluripotency, X chromosome inactivation and nuclear transport. As high throughput sequencing technology develops, a substantial number of lncRNAs have been found to be related to a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 151 publications
0
15
0
Order By: Relevance
“…In these years, lncRNAs, which were considered as byproducts of RNA polymerase II, have emerged to play important roles in regulating various physiological and pathological processes ( Jain et al, 2022 ; Lin et al, 2022 ). In addition, more and more studies have demonstrated that lncRNAs are closely associated with the occurrence and development of tumors, aging, and inflammation, with the rapid development of molecular biology and genetic diagnostic techniques ( Klapproth et al, 2021 ; Zhao et al, 2021 ). A great number of studies have found the dysregulation of lncRNAs and mRNAs involved in many cell-signaling pathways and participated in the occurrence and development of UL ( Nothnick, 2016 ; Lin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these years, lncRNAs, which were considered as byproducts of RNA polymerase II, have emerged to play important roles in regulating various physiological and pathological processes ( Jain et al, 2022 ; Lin et al, 2022 ). In addition, more and more studies have demonstrated that lncRNAs are closely associated with the occurrence and development of tumors, aging, and inflammation, with the rapid development of molecular biology and genetic diagnostic techniques ( Klapproth et al, 2021 ; Zhao et al, 2021 ). A great number of studies have found the dysregulation of lncRNAs and mRNAs involved in many cell-signaling pathways and participated in the occurrence and development of UL ( Nothnick, 2016 ; Lin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of high-throughput sequencing, novel bioinformatics approaches, and corresponding experimental validation, a broad spectrum of mRNAs and lncRNAs have been suggested to play an important role in various biological processes ( Klapproth et al, 2021 ; Lin et al, 2022 ). Long non-coding RNAs (lncRNAs) are a type of long non-coding RNA molecules, more than 200 nucleotides in length, which limited their protein-encoding potential ( Zhao et al, 2021 ). Functionally, accumulating evidences have implicated that lncRNAs are involved in various physiological processes, such as human genome imprinting, chromatin remodeling, X chromosome silencing, epigenetic regulation, and cell cycle and differentiation, and that the abnormal expression and dysfunction of lncRNAs play an functional role in the occurrence and development of a variety of diseases ( Wu et al, 2021 ; Jain et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs are a category of noncoding RNAs with over 200 nucleotides in length, tissue specificity and low species conservation ( Jalaiei et al, 2021 ; Zhao et al, 2021 ). LncRNAs bind to proteins through their unique secondary structure to form RNA-protein complexes ( Dashti et al, 2021 ; Janaththani et al, 2021 ; Mardani et al, 2021 ) and interact with multiple RNAs to form complex gene expression regulatory networks ( Sun and Feinberg 2021 ; Wu et al, 2021 ).…”
Section: The Regulatory Mechanism Of Ncrnas In the Glycolysis Of Ovar...mentioning
confidence: 99%
“…Additionally, lncRNAs affect RNA stability and structure and are also involved in post‐transcriptional processes. These various functions are because they have the potential to interact with DNA sequences; also, they can interact with RNA molecules with complementary sequences and they can bind to a variety of proteins by forming secondary complex structures (Moran et al, 2012; Zhao et al, 2021). Earlier studies showed that several lncRNAs, including NEAT1, MALAT1 , MRH1 , HongrES2 and NLC1‐C were expressed in the male reproductive system, and overexpression of lncRNA HOTTIP was associated with male infertility (Liu, Mao, et al, 2018; Su et al, 2019).…”
Section: Introductionmentioning
confidence: 99%